Lipoprotein metabolism in hepatic lipase deficiency: studies on the turnover of apolipoprotein B and on the effect of hepatic lipase on high density lipoprotein. - Demant, T; Carlson, L; Holmquist, L; Karpe, F; Nilsson-Ehle, P; Packard, C; Shepherd, J (1988)
Hepatic lipase deficiency produces significant distortion in the plasma lipoprotein profile. Particles with reduced electrophoretic mobility appear in very low density lipoprotein (VLDL). Intermediate density lipoprotein (IDL) increases markedly in the circulation and plasma low density lipoprotein (LDL) levels fall. At the same time there is a mass redistribution within the high density lipoprotein (HDL) spectrum leading to dominance in the less dense HDL2 subfraction. The present study examines apolipoprotein B turnover in a patient with hepatic lipase deficiency. The metabolism of large and small very low density lipoproteins was determined in four control subjects and compared to the pattern seen in the patient. Absence of the enzyme did not affect the rate at which large very low density lipoproteins were converted to smaller particles within this density interval (i.e., of VLDL). However, subsequent transfer of small very low density lipoproteins to intermediate density particles was retarded by 50%, explaining the abnormal accumulation of VLDL in the patient's plasma. Despite this, intermediate density particles accumulated to a level 2.4-times normal because their subsequent conversion to low density lipoprotein has been almost totally inhibited. Consequently, the plasma concentration of low density lipoprotein was only 10% of normal. On the basis of these observations, hepatic lipase appears to be essential for the conversion of small very low density and intermediate density particles to low density lipoproteins. The pathways of direct plasma catabolism of these species were not affected by the enzyme defect. In vitro studies were performed by adding purified hepatic lipase to the patient's plasma.(ABSTRACT TRUNCATED AT 250 WORDS)